Bone and Joint Tuberculosis: The Experience From a Tuberculosis Department in Northern Greece - Anastasios Vogiatzoglou; Maria Hadji Mitrova; Eleni Papadaki; Maria Sionidou; Katerina Manika (Case Reports in Infectious Diseases)
Conclusions: TB is a rare cause of infection of bones and joints; however, it should be included in the differential diagnosis of bone lesions. PCR for M. tuberculosis seems to have significantly good results in microbiological confirmation of osteoarticular TB.